Chlorophyll-a transformations associated with sinking diatoms during termination of a North Atlantic spring bloom - Carole Llewellyn (Marine Chemistry, 2015)
A research cruise in the North Atlantic during the annual diatom bloom provided an ideal platform to study chlorophyll-a (chl-a) transformations associated with a large scale diatom bloom and export below the photic zone. On one deployment, Lagrangian sediment traps captured a significant flux of aggregated diatom cells produced during the termination of the main bloom. We examined the distribution of chl-a transformation products in sinking particles from the sediment traps and in suspended particles from the water column using high-resolution HPLC with multistage mass spectrometry (LC-MSn). There was a dramatic change in the distribution of chl-a and its transformation products between the pre-sinking period, when the average chl-a concentration integrated over the upper 50 m was 68 ± 36 mg m-2, and the post-sinking period, when it was 30 ± 11 mg m-2. Before the diatom bloom left the euphotic zone (pre-sinking), suspended particles contained a considerably higher percentage of pheophorbide-a and other chl-a transformation products (27%) than during the post-sinking period (10%). Despite high levels of spatial variability in the chl-a concentration, and despite sampling from both within and outside a main bloom patch, the chl-a transformation products in suspended particles did not exhibit spatial variability. Sinking particles associated with the diatom bloom export had low POC: chl-a ratios (52 - 97), suggesting undegraded phytoplankton cells. However, the samples with especially low POC: chl-a ratios exhibited similar distributions of chl-a transformation products to those with a higher ratio. The proportions of demetalated and de-esterified transformation products increased with depth of suspended particles, although significant levels of these products were also found in the uppermost 20 m during the bloom. This suggests processes in both surface waters and through the water column led to the formation of these products.